2010
DOI: 10.30935/cedtech/5960
|View full text |Cite
|
Sign up to set email alerts
|

Learning Strategies of Successful and Unsuccessful University Students

Abstract: The purpose of this study was to assess the most commonly used learning strategies of undergraduate students and how these strategies were related to their academic performance. Toward this purpose, a 60 item Likert scale was administered to a sample of 278 undergraduate students. The students were selected based on their cumulative grand-point-average as the most successful and the least successful five senior-year students from each majoring area in the faculties of arts, engineering, science, communication,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 12 publications
6
36
0
6
Order By: Relevance
“…It is also crucial to indicate that the analysis of the data reveals that both high and low achievers were found to be meta-cognitively oriented since both high and low achievers used meta-cognitive strategies with the highest preference and with the means of (4.15) and (3.61) respectively. This is consistent with the existing literature of (Abu Shmias, 2003;Al-Buainain, 2010;Saricoban and Saricaoglu, 2008;Simsek & Balaban, 2010;Tajareh and Tahririan, 2003). The high use of meta-cognitive strategies among Yemeni students is similar to that observed among students from Asian countries like Japan, China, Korea and Taiwan as reported in some of the studies on Asian students (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…It is also crucial to indicate that the analysis of the data reveals that both high and low achievers were found to be meta-cognitively oriented since both high and low achievers used meta-cognitive strategies with the highest preference and with the means of (4.15) and (3.61) respectively. This is consistent with the existing literature of (Abu Shmias, 2003;Al-Buainain, 2010;Saricoban and Saricaoglu, 2008;Simsek & Balaban, 2010;Tajareh and Tahririan, 2003). The high use of meta-cognitive strategies among Yemeni students is similar to that observed among students from Asian countries like Japan, China, Korea and Taiwan as reported in some of the studies on Asian students (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Ley and Young (2001) cite two studies (Ley & Young, 1998;Zimmerman & Martinez-Pons, 1986) which report that academically stronger groups used organizing strategies more often than academically weaker groups. Based on research carried out with 278 undergraduate students, Simsek and Balaban (2010) also conclude that the learning strategies used by successful students were more varied and better than those used by unsuccessful students.…”
Section: Learning Strategiesmentioning
confidence: 95%
“…As far as gender is concerned, although female students have been shown to apply more strategies and do so more often and more effectively than male students (Macaro, 2001;Simsek & Balaban, 2010;Zeynali, 2012), Oxford and Ehrman (1990) point out that psychological type, such as being Thinkers of Feelers, is an even more important variable.…”
Section: Learning Strategiesmentioning
confidence: 99%
“…After Carton in 1971, Rubin (1975) started doing research focusing on the strategies of successful learners and stated that, once identified; such strategies could be made available to less successful learners. Rubin(1987Rubin( ) O'malley (1985, Oxford(1990), Brown(2002Simsek (2006;2010) have greatly contributed in the classification and promotion of language learning strategies.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Gu(2005) in this context, argues that it is difficult to find out and it is not clear about the bases of selecting particular strategies and preference on them rather than others. In this vein, Simsek and Balaban(2010) urge not to feel surprise looking various strategies employed by the students because each student is guided by instructional variables like technology, exposure, time, teaching methods, subject matters, feedback, individual differences , evaluation system and so forth.…”
Section: Introductionmentioning
confidence: 99%